PERBEDAAN PERSEPSI PENGANTAR KEARIFAN SOLUSI - Harjanto, Rudy (Universitas Prof. Dr. Moestopo (Beragama), 2008)
Advertising activity in practice should be conducted in full manner of social responsibility due to differentiated of perception. The appearance of advertisements expected to be executed in line with ethics, and consumerism regulatory. Negative perceptions on advertising should be taken as control tools how to make advertisements could contribute in better way to society The difference perceptions bridge wisdom of solution.